Ответ:
на фото все решение есть
Пошаговое объяснение:
2,5х = -1
х = -1 : 2,5
х = -0,4
0,3х = 1
х = 1 : 0,3
х = 1 : 3/10
х = 1 * 10/3
х = 10/3
х = 3 1/3
|х| - 5 = 0
|х| = 0 + 5
|х| = 5
х1 = -5
х2 = 5
|х| + 3,2 = 8
|х| = 8 - 3,2
|х| = 4,8
х1 = -4,8
х2 = 4,8
8/х = 6/5
6 * х = 5 * 8
6х = 40
х = 40 : 6
х = 40/6
х = 20/3
х = 6 2/3
7/4 = х/2
4 * х = 7 * 2
4х = 14
х = 14 : 4
х = 3,5
3(1 - х) + 5(х + 2) = 1 - 4х
3 - 3х + 5х + 10 = 1 - 4х
2х + 13 = 1 - 4х
2х + 4х = 1 - 13
6х = -12
х = -12 : 6
х = -2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
на фото все решение есть
Verified answer
Пошаговое объяснение:
2,5х = -1
х = -1 : 2,5
х = -0,4
0,3х = 1
х = 1 : 0,3
х = 1 : 3/10
х = 1 * 10/3
х = 10/3
х = 3 1/3
|х| - 5 = 0
|х| = 0 + 5
|х| = 5
х1 = -5
х2 = 5
|х| + 3,2 = 8
|х| = 8 - 3,2
|х| = 4,8
х1 = -4,8
х2 = 4,8
8/х = 6/5
6 * х = 5 * 8
6х = 40
х = 40 : 6
х = 40/6
х = 20/3
х = 6 2/3
7/4 = х/2
4 * х = 7 * 2
4х = 14
х = 14 : 4
х = 3,5
3(1 - х) + 5(х + 2) = 1 - 4х
3 - 3х + 5х + 10 = 1 - 4х
2х + 13 = 1 - 4х
2х + 4х = 1 - 13
6х = -12
х = -12 : 6
х = -2